A Bibliometric Analysis of the Role of Cultural Diversity in Multinational Management - Loso Judijanto; Siminto Siminto; Bayu Purbha Sakti (West Science Social and Humanities Studies, 2024)
Cultural diversity within multinational management is a pivotal area of study with profound implications for organizational effectiveness, innovation, and performance. This open-access article presents a comprehensive bibliometric analysis conducted to synthesize and evaluate the current state of knowledge in this field. Utilizing systematic literature review and bibliometric techniques, we identify and analyze 910 scholarly articles spanning from 1965 to 2024, with a total of 232,210 citations. The analysis reveals enduring scholarly interest, as evidenced by an average citation rate of 3,935.76 cites per year. Top cited research articles highlight seminal contributions that have significantly shaped our understanding of cultural diversity in multinational contexts. Network and overlay visualizations unveil evolving research trends, identifying clusters of interest and emerging areas for future investigation. The findings not only provide a comprehensive overview of existing literature but also offer insights into promising avenues for further research, ultimately contributing to improved organizational performance and intercultural collaboration in the global marketplace.